COMMUNITY EMPOWERMENT THROUGH PRODUCTIVE WAQF IN LAMPUNG PROVINCE: THE ROLE OF BWI, NAZHIR, AND LOCAL WISDOM - Erwinto, Erwinto; Hs, Achlami; Jauhari, Tantowi; Hilal, Syamsul (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Objective: This study analyzes the contribution of productive waqf to community economic empowerment in Lampung Province, highlighting the role of Indonesian Waqf Board (BWI) representatives, nazhir, and the influence of local social norms and cultural values. Method: The research approach used a qualitative descriptive-analytical method through in-depth interviews, participant observation, and documentation studies in Central Lampung and Pesawaran Regencies. Results: The results show that productive waqf management is developing through the utilization of waqf land assets, cash waqf collection, and collaboration with LKS-PWU and community business models such as collective farming and social retail. The main challenges include low waqf literacy, limited managerial capacity of nazhir, and less than optimal regulatory support and institutional networks. The integration of local values ​​such as fi’il pesenggiri and the sabilillah tradition strengthens social legitimacy and community participation. Conclusion: These findings confirm that productive waqf has the potential to become a sustainable community-based empowerment instrument if managed professionally, transparently, and adaptively to local wisdom. Implications: The implications of this study can be a reference for the development of productive waqf policies and practices in other regions, both in Indonesia and countries with similar social characteristics.